Exercise and Type 1 Diabetes (T1DM). Issue 3 (July 2013) - Galassetti, Pietro; Riddell, Michael C.
Abstract: Physical exercise is firmly incorporated in the management of type 1 diabetes (T1DM), due to multiple recognized beneficial health effects (cardiovascular disease prevention being preeminent). When glycemic values are not excessively low or high at the time of exercise, few absolute contraindications exist; practical guidelines regarding amount, type, and duration of age‐appropriate exercise are regularly updated by entities such as the American Diabetes Association and the International Society for Pediatric and Adolescent Diabetes. Practical implementation of exercise regimens, however, may at times be problematic. In the poorly controlled patient, specific structural changes may occur within skeletal muscle fiber, which is considered by some to be a disease‐specific myopathy. Further, even in well‐controlled patients, several homeostatic mechanisms regulating carbohydrate metabolism often become impaired, causing hypo‐ or hyperglycemia during and/or after exercise. Some altered responses may be related to inappropriate exogenous insulin administration, but are often also partly caused by the "metabolic memory" of prior glycemic events. In this context, prior hyperglycemia correlates with increased inflammatory and oxidative stress responses, possibly modulating key exercise‐associated cardio‐protective pathways. Similarly, prior hypoglycemia correlates with impaired glucose counterregulation, resulting in greater likelihood of further hypoglycemia to develop. Additional exercise responses that may be altered in T1DM include growth factor release, which may be especially important in children and adolescents. These multiple alterations in the exercise response should not discourage physical activity in patients with T1DM, but rather should stimulate the quest for the identification of the exercise formats that maximize beneficial health effects. © 2013 American Physiological Society. Compr Physiol 3:1309‐1336, 2013.